A compreensão das práticas educativas no contexto familiar sob, o olhar de crianças: um estudo fenomenológico - Gomes, Bruna Maria Souza (2009)
This paper aimed to investigate how family educational practices are perceived by children. The study was based on the existential conception of the human being, in a context of co-existence and as a pro-ject. It was adopted the ideas of Merleau-Ponty s about chilhood, considered as a plural phenomenum. It is also considered sociological studies of childhood as well as the dialogical practice of Paulo Freire s humanize educational process. It is a qualitative phenomenological research, developed with nine participants from the fourth grade of a public school. Procedures envolved a first moment as a group conversation and, after that, there was a warm up, in which the children had to choose and describe a picture of a family among many pictures of different families structures. In addition, as a group, they had to draw a family and discuss about it. The data analysis revealed theconceptions of educational practices for those children. The results showed that they had reproduced properly their own families educationalpractices. They basically cared about the little ones and the eldest children were the ones responsable for it. The educational usage shows an authoritarian kind of education. The dialogical practice of education is shown as a desire, and this finding it lead to a new perspective of work with families and children based on a humanized education, a better relationship among human beings, however not denying parents authority